Trace element concentrations and their potential ecological risk in the reef sediments of coral islands, Vembar group of islands, Gulf of Mannar, India. (November 2020) - Pradhap, D.; Gandhi, K. Sanjai; Magesh, N.S.; Peter, T. Simon; Sadhu, C.; Silva, Judith D.; Godson, Prince S.; Krishnakumar, S.; Saravanan, P.
Abstract: The present work was undertaken to assess the impact of trace element concentration and the status of potential ecological risk in the reef sediments of the Vembar group of islands, Gulf of Mannar Marine National Park, India. Totally, 114 reef sediments (surface) were collected from the Vembar group of islands (Nallathanni Island – 36 samples; Upputhanni Island – 48 samples; Puluvinichalli Island-30 samples). The reef sediments are enriched with sand-sized calcareous particles. The calcium carbonate percentage (CaCO3 ) was primarily controlled by the distribution of coral colonies and available lithogenic grains. The pollution load index (PLI) reveals that the majority of the sediments fall under the unpolluted category. Moreover, the potential ecological risk (PERI) and sediment pollution index (SPI) reveals that the Vembar group of islands fall under the low ecological risk category. Highlights: The present study was carried out to study the potential ecological risk status of Vembar group of Islands, Gulf of Mannar The pollution load index (PLI) reveals that the majority of the sediments are under unpolluted category. The potential ecological risk (PERI) and sediment pollution index (SPI) reveals that the Vembar group of Islands is under low ecological risk.